Emphasizing the vitality of genomics related research in the area of infectious diseases - Wayengera, Misaki; Byarugaba, Wilson (Scientific Research and Essays, 2007)
Sequencing of the human and other species genomes has generated a downstream of sciences that have taken advantage of this knowledge to generate vital links between diseases and genetic variants. Sub-Saharan Africa and many developing countries form the major epicenters for Infectious diseases. Here, the role that genomics may hold in the area of infectious diseases research is emphasized in five blocks: phenotype evaluation studies, evolutionary trends’ studies across microbial and host genomes, idiopathic association or host susceptibility studies to disease, therapeutics or vaccine research insights, as well as the development of novel molecular diagnostics.
Keywords: Genomics; Infectious diseases; HIV/AIDS; Malaria; Tuberculosis